Meta-analysis reveals variations in microbial communities from diverse stony coral taxa at different geographical distances - Pei, Peng-Tao; Liu, Lu; Jing, Xiao-Li; Liu, Xiao-Lu; Sun, Lu-Yang; Gao, Chen; Cui, Xiao-Han; Wang, Jing; Ma, Zhong-Lian; Song, Shu-Yue; Sun, Zhi-Hua; Wang, Chang-Yun (Frontiers in Microbiology, 2023)
Coral-associated microbial communities play a vital role in underpinning the health and resilience of reef ecosystems. Previous studies have demonstrated that the microbial communities of corals are affected by multiple factors, mainly focusing on host species and geolocation. However, up-to-date, insight into how the coral microbiota is structured by vast geographic distance with rich taxa is deficient. In the present study, the coral microbiota in six stony coral species collected from the coastal area of three countries, including United States of America (USA), Australia and Fiji, was used for analysis. It was found that the geographic influence on the coral microbiota was stronger than the coral host influence, even though both were significant. Interestingly, the contribution of the deterministic process to bacterial community composition increased as geographical distance grew. A total of 65 differentially abundant features of functions in coral microbial communities were identified to be associated with three geolocations. While in the same coastal area of USA, the similar relationship of coral microbiota was consistent with the phylogenetic relationship of coral hosts. In contrast to the phylum Proteobacteria, which was most abundant in other coral species in USA, Cyanobacteria was the most abundant phylum in Orbicella faveolata. The above findings may help to better understand the multiple natural driving forces shaping the coral microbial community to contribute to defining the healthy baseline of the coral microbiome.